Optimalisasi Profesionalisme Guru-guru PPKn SMA Se-Kota Surabaya Melalui Pelatihan Penulisan Artikel Ilmiah dan Cara Publikasi - Suyono, Suyono; Suhari, Suhari; Bernadetta Budi Lestari; Romadhon, Romadhon; Nehru Firdaus Ardhana; Yani Septia Rachmawati (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
The purpose of the article writing program and publication strategy for PPKn high school teachers in the city of Surabaya is to support Surabaya teachers who do not understand article writing. This program aims to increase knowledge and improve the quality of writing for PPKn teachers, as well as support the process of applying for promotion. This training uses methods, including lectures, discussions, and simulations. The subjects of the training were 29 PPKn high school teachers throughout the city of Surabaya. The purpose of this training is to motivate teachers to be more motivated in writing scientific articles and understanding how to publish. In addition, teachers will gain skills in writing articles and understanding the publishing process so as to improve their professionalism.